Human Fibrinogen Adsorption on Latex Particles at pH 7.4 Studied by Electrophoretic Mobility and AFM Measurements - Bratek-Skicki, Anna; Zeliszewska, Paulina; Adamczyk, Zbigniew (Current Topics in Medicinal Chemistry, 2014)
Human fibrinogen adsorption on negatively charged latex particles was investigated using the electrophoretic and the concentration depletion methods. Measurements were conducted at pH 7.4 and in the range of ionic strength of 10-3 - 0.15 M NaCl. Firstly, the bulk physicochemical properties of fibrinogen were characterized. The zeta potential and the uncompensated (electrokinetic) charges of the protein were determined from the electrophoretic measurements. Next, systematic experiments were performed to determine the dependencies of the electrophoretic mobility of latex on the amount of adsorbed protein. Electrophoretic mobility increased significantly upon fibrinogen adsorption that was proven irreversible. The maximum coverage of fibrinogen on latex particles determined via the concentration depletion method varied between 1.9 mg m-2 and 3.2 mg m-2 for 10-3 and 0.15 M NaCl, respectively. The changes in the maximum coverage were interpreted as due to electrostatic repulsion among adsorbed protein molecules. Additionally, the stability of latex covered by fibrinogen was determined. It was proven that cyclic changes of ionic strength from 10-3 to 0.15 M NaCl did not change the electrophoretic mobility. Based on these observations, it was concluded that there were no conformational changes within adsorbed fibrinogen molecules. The experimental data, allowed one to elaborate a robust procedure of preparing latex particles covered by fibrinogen of designed coverage and molecule distribution.
Keywords: zeta potential of fibrinogen covered latex